VR-Based Workplace Training and Spaces of Learning: A Social Space Study of VR Training for Apprentice Electricians - Katrin Kraus; Martin Berger; Thomas Keller; Elke Brucker-Kley (International Journal for Research in Vocational Education and Training)
Context: This study uses a social space approach to investigate Virtual Reality (VR)-based workplace learning in the context of apprenticeship training in the electronics industry in Switzerland. It was one part of a project which developed a prototype VR environment that enables apprentices to practice testing an electrical installation in a virtual garage using VR headsets. The study uses a spatial theory perspective to understand how the apprentices use the VR environment to develop their vocational competence and how spaces of learning are created through this process.